Translating with Purpose: The Functionality Paradigm - Mangher (Chitac), Ana-Maria (Journal of Danubian Studies and Research, 2023)
The present paper aims to explore the functional approach to translation, which focuses on the purpose, function and intended effect of the translated text. The main proponents of the functionalist approaches Katharina Reiss, Hans Vermeer, Christiane Nord acknowledge that translation does not imply only linguistic correspondence between the target and source text and promote the idea according to which it is the communicative function of the text in the target culture that determines the method of translation. They start from the assumption that the text-type allows the translator to recognize the function and the purpose of the text as well as the author’s intention. Thus, s/he will inevitably resort to different techniques and strategies in order to successfully render the source text meaning into the target language. The examination of the most important studies related to this approach has provided us the theoretical framework that will serve as a foundation for our research: the translation of medical/pharmaceutical texts.